Trabajo nocturno: ¿podemos prevenir sus efectos adversos en la salud? - Manolis Kogevinas (Archivos de Prevención de Riesgos Laborales)
Night-shift work has become a structural component of modern economies, supporting essential services from healthcare and transportation to logistics and manufacturing. But with this systemic need comes a significant burden on health. Mounting evidence links night-shift work to a wide range of adverse outcomes, from acute fatigue to chronic diseases including cancer. While scientific understanding of its mechanisms has grown rapidly, preventive policies — both at institutional and individual levels — have lagged behind. In this article, I argue that the health consequences of night-shift work are no longer an occupational hazard to be suffered, but a modifiable public health issue requiring targeted prevention strategies…